Model Matematika Penyebaran Penyakit Kanker Serviks dengan Pengobatan Kemoterapi - Siti Aminah; Muhammad Subhan (UNIVERSITAS NEGERI PADANG, 2022)
Cervical cancer.is a disease that attacks the female.reproductive organs and often occurs in Indonesian women. Cervical cancer occurs because of a change from normal cervical cells to abnormal cervical cells and can turn into benign tumors and malignant tumors. The purpose of the reseach is to study the mathematical model of cervical cancer by chemotherapy treatment or to determine the effect of chemotherapy on cell growth in cervical cancer. The author performs a stability analysis on the fixed point model where there are two fixed points. The results of this study are that cervical cancer treatment with chemotherapy is effective enough to kill abnormal cells, although there are side effects, namely the killing of normal cells.